2014 IEEE International Conference on Mechatronics and Automation 2014
DOI: 10.1109/icma.2014.6885852
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new statically balanced parallel mechanisms

Abstract: In this paper, a method for type synthesis of several new statically balanced parallel manipulators is presented systematically. Firstly, using the concept of constant potential energy, we propose a statically balanced stackable planar mechanism. Secondly, based on the statically balanced stackable planar mechanism, independent statically balanced limb types with certain constraint are designed. Thirdly, combining specific limbs with different wrench system, we synthesize several n-DOF (degree of freedom) para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Manipulator paralel menggunakan rantai paralelogram simetris yaitu 2-ΠΠΠ dan 2-ΠΠ yang dibahas dalam tulisan ini memiliki konfigurasi rantai kinematik seperti yang ditunjukkan dalam Gambar 1. Manipulator paralel bidang 2-ΠΠΠ pada Gambar 1 sedikit berbeda dengan konstruksi yang telah disintesis oleh Kang, dkk [14]. Parameter geometri kedua manipulator ini juga diberikan dalam Gambar 1 berikut dengan sistem kerangka acuan tetap XOY di base dan kerangka acuan bergerak xPy di platform manipulator.…”
Section: Metodeunclassified
“…Manipulator paralel menggunakan rantai paralelogram simetris yaitu 2-ΠΠΠ dan 2-ΠΠ yang dibahas dalam tulisan ini memiliki konfigurasi rantai kinematik seperti yang ditunjukkan dalam Gambar 1. Manipulator paralel bidang 2-ΠΠΠ pada Gambar 1 sedikit berbeda dengan konstruksi yang telah disintesis oleh Kang, dkk [14]. Parameter geometri kedua manipulator ini juga diberikan dalam Gambar 1 berikut dengan sistem kerangka acuan tetap XOY di base dan kerangka acuan bergerak xPy di platform manipulator.…”
Section: Metodeunclassified
“…Kim and Cho [13] proposed a static balancing mechanism for a face robot that uses a gravity compensator (spring). Using the concept of constant potential energy, Kang et al [14] proposed a statically balanced stackable planar mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The stiffness model of the balancing mechanism was found as the measure of the open-loop stability, and zero stiffness ensured static balancing over the entire workspace of the mechanism. Seo et al [33] described balancing methods for a passive surgical robot, and Kang et al [14] also did so for a parallel robot that was designed on the basis of a stackable parallel mechanism. Balancing equations for the stackable mechanism were suggested that ensured gravity compensation in the entire workspace of the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, gravity balanced mechanisms design with parallelograms were widely discussed in previous researches. [22][23][24][25][26] Moreover, type synthesis of new statically balanced PM by using a stackable planar mechanism 27 as the building block was investigated by Kang et al 28 Based on previous studies, 27,28 a kind of gravity balanced 3T1R-PM is proposed and deeply investigated in this work. This PM is composed of two limbs.…”
Section: Introductionmentioning
confidence: 99%